But Who Will Monitor the Monitor? - Rahman, David (American Economic Review, 2012)
Suppose that providing incentives for a group of individuals in a strategic context requires a monitor to detect their deviations. What about the monitor's deviations? To address this question, I propose a contract that makes the monitor responsible for monitoring, and thereby provides incentives even when the monitor's observations are not only private, but costly, too. I also characterize exactly when such a contract can provide monitors with the right incentives to perform. In doing so, I emphasize virtual enforcement and suggest its implications for the theory of repeated games. (JEL C78, D23, D82, D86)